Adrenergic Regulation of HCN4 Channel Requires Protein Association with β(2)-Adrenergic Receptor - Greene, Derek (American Society for Biochemistry and Molecular Biology, 2012)
β(1)- and β(2)-adrenergic receptors utilize different signaling mechanisms to control cardiac function. Recent studies demonstrated that β(2)-adrenergic receptors (β(2)ARs) colocalize with some ion channels that are critical for proper cardiac function. Here, we demonstrate that β(2)ARs form protein complexes with the pacemaker HCN4 channel, as well as with other subtypes of HCN channels. The adrenergic receptor-binding site was identified at a proximal region of the N-terminal tail of the HCN4 channel. A synthetic peptide derived from the β(2)AR-binding domain of the HCN4 channel disrupted interaction between HCN4 and β(2)AR. In addition, treatment with this peptide prevented adrenergic augmentation of pacemaker currents and spontaneous contraction rates but did not affect adrenergic regulation of voltage-gated calcium currents. These results suggest that the ion channel-receptor complex is a critical mechanism in ion channel regulation.